Bioprospecting microalgae harnessed from the coastal belt of Mangalore, India as prospective nutraceutical and biofuel candidates. Issue 1 (1st January 2021) - Karkala, Sulakshana; D'Souza, Leo; Nivas, Shashi kiran
ABSTRACT: The nature of global dietary supplements is transitioning from animal derivatives to plant based. Industries around the world are seeking vegan alternatives to animal-derived supplements. The microalgal industry is expected to undergo a market boom in the current decade. Microalgal supplements (power based and extracts) as well as microalgal fuels are expected to show a significant increase in market value. Microalgae are an under-utilized source of high-value products. They are rich reservoirs of multiple compounds capable of enhancing immunity, fortifying nutritional diets and improving cardiovascular health. Microalgae are also high lipid producing organisms, which make them viable candidates in the global search for energy alternatives. However, the inability to translate in vitro results onto the industrial scale is a major drawback of the microalgal research landscape. It is therefore, vital to find a robust microalgal species capable of producing a feasible quantity of high-value compounds. This paper investigates the potential of four microalgae sourced from the coastal town of Mangalore, India as candidates for nutraceutical industries and the clean energy industry. Desmodesmus komareikii (MK990101) was found to be rich in total lipid, while the three Chlorella species were found to be relatively richer in total protein yields. Chlorella thermophila (MN006612) is capable of yielding harvests up to nearly 280 tonnes/acre/year. Chlorella thermophila (MN006612) yielded the highest amount of both mono and polyunsaturated fatty acids. The fatty acid profiles of Chlorella thermophila (MN006612), Chlorella vulgaris (MN252517-18) and Chlorella sorokiniana (MN011568) can be explored as an alternative edible oil. Desmodesmus komareikii (MK990101) yielded the highest amount of saturated fatty acids, which are used in the production of clean and quality biofuels.